Comparative assessment of a Chinese indigenous entomopathogenic nematode versus a commercial strain for the biological control of Spodoptera frugiperda - Zeng, ShuoCheng; Zhang, Haiting; Yi, Jun; Fu, Huijuan; Ji, Zhengyu; Chen, Cheng; Shapiro-Ilan, David; Li, Xingyue (Biological control, 2025)
•First investigation of EPN resources in Chongqing region of southwestern China.•Novel H. indica CQ7-2 population demonstrates remarkable virulence for S. frugiperda.•The H. indica CQ7-2 population exhibits superior heat tolerance. Entomopathogenic nematodes (EPNs) have gained recognition for their effectiveness as environmentally friendly biological control agents and have seen widespread commercialization worldwide. Research into screening local EPN strains with high virulence and resistance is important due to the challenges posed by the expanding range of pests from invasive species and complex environmental conditions. We have recently discovered a native population of Heterorhabditis indica (Rhabditida: Heterorhabditidae) in Chongqing, an area that has not been previously surveyed for EPN resources, which we have designated as CQ7-2. Notably, the domestic commercial EPN market in China is currently limited, with Steinernema feltiae being the primary commercial product available; therefore, we selected this commercialized species as the benchmark for comparing our newly isolated H. indica strain. We assessed its heat tolerance and biocontrol potential against the invasive pest Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) and compared its performance with that of this commercially relevant comparator. This population CQ7-2 can maintain a survival rate of over 88 % for over 40 h at 36 °C and more than 75 % at 38 °C up to 8 h. The results of bioassays demonstrated that the median lethal concentration (LC50) value of this particular EPN strain against Galleria mellonella (Lepidoptera: Pyralidae) larvae was corresponding to a dose of 2.92 IJs/larva, while it exhibited LC50 values corresponding to doses of 5.79 IJs/larva and 6.65 IJs/larva against third and sixth instar larvae of S. frugiperda respectively. Overall, the newly isolated indigenous EPN H. indica population (CQ7-2) showed excellent control efficacy against the invasive pest S. frugiperda, and when combined with its exceptional heat resistance, it has the potential to be an effective tool for integrated pest management.